A CONSTRUÇÃO DO FUTURO E A REDIMENSÃO DO PASSADO (Revista de História Regional, 2007)
This article aims at presenting an analysis of the unfolding of the social practice and representation of wage earners from the sugar cane agro-industry in Campos, Rio de Janeiro, into agricultural producers warded by institutions linked to the politics of agrarian reform.